Knowledge, attitude, and practice of butchers regarding Crimean-Congo hemorrhagic fever in an endemic area of Iran - Amin Gorouhi, Mohammad; Aghaei Afshar, Abbas; Mansoori, Najmeh; Jangipour Afshar, Parya; Shirani-Bidabadi, Leila; Alizadeh, Ismaeil; Shahhosseini, Nariman (Chulalongkorn Medical Journal, 2025)
Background: Crimean-Congo hemorrhagic fever (CCHF) is an important zoonotic disease, particularly in endemic countries, with considerable public health implications. Previous studies in Iran suggest that CCHF poses a substantial health risk to slaughterhouse workers and butchers. Objective: To investigate the knowledge, attitude, and practice of butchers regarding CCHF at their place of work in an endemic area in Southeastern Iran. Methods: Data collection was performed using a convenience sampling method. The study included 60 eligible butchers from Zarand City. Data were collected using a questionnaire, and statistical analysis was performed using SPSS version 22. Results: The average scores of the participants’ knowledge, attitude, and practice were 2.6 ± 1.5, 25.4 ± 3.2, and 21.8 ± 4.1, respectively, indicating most butchers had good knowledge of and a positive attitude toward and practice regarding CCHF safety measures. There was no significant difference between the participants’ knowledge, attitude, and practice in relation to the studied variables. However, Pearson correlations revealed significant positive correlations between knowledge and attitude (r = 0.345), between knowledge and practice (r = 0.295), and between practice and attitude (r = 0.361) with regard to CCHF disease. Conclusion: The current study results can help prevent occupational health risks related to work-acquired CCHF among butchers. We recommend that more comprehensive studies be conducted to evaluate other occupations that are at high risk of acquiring CCHF in Iran.